Analisis Kajian Yuridis Undang-Undang Nomor 19 Tahun 2016 Tentang Kasus Perjudian Online Tranding Binomo - Alfata, Muhammad Dhoyfullah; Handayani, Budi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of digital technology has had a significant impact on various aspects of life, including the economic and trade sectors. One of the phenomena that has been highlighted is the rise of online trading platforms such as Binomo, which in practice is often categorized as gambling under the guise of investment. This study aims to analyze the legal aspects of online gambling cases involving the Binomo platform based on Law Number 19 of 2016 concerning Electronic Information and Transactions (UU ITE) and other related regulations in the legal system in Indonesia. This study uses a normative legal method with a statute approach and a case approach. The results of the study show that the Binomo platform has a transaction mechanism that resembles gambling, where users risk funds in the hope of getting big profits in a short time, but without transparent and accountable control. Based on Article 27 paragraph (2) of the ITE Law, activities that contain elements of gambling are strictly prohibited in Indonesia, and violations of this provision can be subject to criminal sanctions. In addition, from a trade law perspective, Binomo does not have an official permit from the Financial Services Authority (OJK) and the Commodity Futures Trading Supervisory Agency (BAPPEBTI), so all its activities in Indonesia are illegal. Furthermore, this study reveals challenges in enforcing the law against online gambling, including obstacles in supervision, minimal digital literacy among the public, and the complexity of taking action against foreign-based platforms. Therefore, a stricter policy is needed in regulating online trading platforms, increased international cooperation in eradicating cybercrime, and more massive education for the public regarding the risks of illegal investment.